Cultivation of Furcraea foetida ([L.] Haw.) under different nitrogen doses and sources - Girardi, Leonita Beatriz; Menegaes, Janine Farias; Backes, Fernanda Alice Antonello Londero; Bellé, Rogério Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The ornamental plant sector is diversified and demanding in terms of quality, which includes plant nutrition. Thus, the objective of this work was to evaluate the leaf development of F. foetida var. Striata cultivated in a greenhouse under different nitrogen dosages and sources. A completely randomized experimental design was used, in a 3×3+1 factorial scheme, nitrogen doses were 100, 200 and 300 mg L-1 and sources with different nitrogen percentages: calcium nitrate, ammonium nitrate and urea, plus the additional treatment (control: no treatment), with six replications. The number of leaves, length, width and leaf area were evaluated. It was observed that there was full leaf development of plants grown in pots, at 390 days after transplanting, the plants had average parameters of 10.4 leaves/plant, 36.9 cm in leaf length and 6.3 cm leaf width. It was concluded that the different nitrogen doses and sources favored the quality of leaf development of F. foetida, preserving their ornamental characteristics in terms of shape and plasticity.